FAʿĀLĪAẗI WASĪLAẗI SPINNING WHEEL FĪ TAḤSĪNI NATĀIJI TAʿLĪMI AL-NAḤWI FĪ AL-MADRASATI AL-MUTAWASSITHAH AL-ISLĀMĪAH BUSTĀNU AL-ʿULŪM AL-SURŪR SŪMBER JAMBE LIL SANATI AL-DIRĀSĪYATI 2022/2023 M - Muqit, Abdul; Ruswatie, Ade (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2023)
Spinning wheel learning media is a learning media in the form of a spinning wheel containing questions that combines the ability to answer questions with the insights that students already have. As a result of personal interviews with Arabic teachers, researchers obtained academic information that there are still many students who have difficulty learning Arabic, especially in qawaid nahwu. The researcher took the title of this study because of the problems that occur among students who lack enthusiasm in learning nahwu so that learning outcomes are not optimal. Therefore, researchers consider that spinning wheel learning media is very suitable for this problem. The purpose of this study are: To determine the effectiveness of Spinning Wheel learning media in improving nahwu learning outcomes. Researchers use quantitative research approaches and types of experimental research, as well as data collection methods through observation, tests, and documentation. Data analysis method using t-test code. The results of this research mean the application of spinning wheel learning media to improve learning outcomes nahwu there are differences in the learning outcomes of the control group and the experimental group. Thus the spinning wheel learning